Expert Perceptions of the Development of Maqāṣid al-Sharīʿah in Indonesian Islamic Law: Explaining the Epistemic–Institutional Gap - Tholkhatul Khoir; Abdul Djamil; Kamsi; Imam Yahya; Hamdan bin Said (Al-Mazaahib: Jurnal Perbandingan Hukum, 2026)
Over the past two decades, maqāṣid al-sharīʿah has gained increasing prominence in Indonesian Islamic legal scholarship and legal discourse, including legislation, fatwas, judicial decisions, and academic publications. Although this development has been widely examined in normative legal scholarship, little empirical research has investigated how Islamic law experts perceive this trend and its implications for legal reform. This study explores how Indonesian Islamic law academics and practitioners perceive the development of maqāṣid al-sharīʿah in Indonesian Islamic law and examines the factors shaping these perceptions. Employing a qualitative exploratory design and drawing on Berger and Luckmann’s theory of the social construction of knowledge as its primary theoretical lens, this study conducted semi-structured interviews with five purposively selected Islamic law academics and practitioners whose scholarly and professional roles position them as epistemic authorities in Indonesian Islamic legal discourse. Data were analysed using reflexive thematic analysis. The findings indicate that differences in expert perceptions are shaped by the interaction of methodological orientation, professional engagement, academic literacy, and exposure to contemporary social issues. Rather than operating independently, these factors interact to shape how experts evaluate the extent to which maqāṣid has moved beyond academic discourse into institutional legal practice. The findings suggest the existence of an epistemic–institutional gap in which the intellectual acceptance of maqāṣid has progressed more rapidly than its incorporation into formal legal institutions. By identifying the interaction of multiple factors shaping expert perceptions, this study contributes empirical and conceptual insights into the relationship between epistemic development and institutional change in contemporary Indonesian Islamic law. Selama dua dekade terakhir, maqāṣid al-sharīʿah semakin menonjol dalam kajian hukum Islam dan wacana hukum di Indonesia, termasuk legislasi, fatwa, keputusan pengadilan, dan publikasi akademis. Meskipun perkembangan ini telah banyak dikaji dalam kajian hukum normatif, hanya sedikit penelitian empiris yang menyelidiki bagaimana para ahli hukum Islam memandang tren ini dan implikasinya terhadap reformasi hukum. Studi ini mengeksplorasi bagaimana akademisi dan praktisi hukum Islam di Indonesia memandang perkembangan maqāṣid al-sharīʿah dalam hukum Islam Indonesia dan mengkaji faktor-faktor yang membentuk persepsi tersebut. Dengan menggunakan desain kualitatif eksploratif dan teori konstruksi sosial pengetahuan Berger dan Luckmann sebagai lensa teoretis utama, studi ini melakukan wawancara semi-terstruktur dengan lima akademisi dan praktisi hukum Islam yang dipilih secara purposif. Peran akademis dan profesional mereka menempatkan mereka sebagai otoritas epistemik dalam wacana hukum Islam di Indonesia. Data dianalisis menggunakan analisis tematik refleksif. Temuan menunjukkan bahwa perbedaan persepsi para ahli dibentuk oleh interaksi orientasi metodologis, keterlibatan profesional, literasi akademis, dan paparan terhadap isu-isu sosial kontemporer. Alih-alih beroperasi secara independen, faktor-faktor ini berinteraksi untuk membentuk bagaimana para ahli mengevaluasi sejauh mana maqāṣid telah melampaui wacana akademis ke dalam praktik hukum institusional. Temuan ini selanjutnya menunjukkan adanya kesenjangan epistemik–institusional di mana penerimaan intelektual terhadap maqāṣid telah berkembang lebih cepat daripada penggabungannya ke dalam lembaga hukum formal. Dengan mengidentifikasi interaksi berbagai faktor yang membentuk persepsi para ahli, studi ini memberikan wawasan empiris dan konseptual tentang hubungan antara perkembangan epistemik dan perubahan institusional dalam hukum Islam kontemporer di Indonesia.